2021
DOI: 10.1093/cz/zoab074
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing reveals dietary segregation in Malaysian babblers

Abstract: The coexistence of numerous species within a community results from how those species use available resources. Babblers are one of the major groups of Malaysian insectivorous birds, which frequently forage in dense vegetation cover and have a high level of sympatry. Therefore, examining the diet, prey selection and niche segregation of babblers can be challenging. In this study, we used high-throughput sequencing to investigate potential dietary overlap or segregation among 10 babbler species of the four gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Both protein and lipids (e.g., fats) are crucial for bird growth (Klasing 2000). Diet overlaps among babblers in this study were relatively low, consistent with reports from central Peninsular Malaysia (Mansor et al 2018(Mansor et al , 2021. The differences noted in foraging tactics might be one of the factors influencing the diet of the babbler species and vice versa.…”
Section: Diet Compositionsupporting
confidence: 89%
See 1 more Smart Citation
“…Both protein and lipids (e.g., fats) are crucial for bird growth (Klasing 2000). Diet overlaps among babblers in this study were relatively low, consistent with reports from central Peninsular Malaysia (Mansor et al 2018(Mansor et al , 2021. The differences noted in foraging tactics might be one of the factors influencing the diet of the babbler species and vice versa.…”
Section: Diet Compositionsupporting
confidence: 89%
“…Being terrestrial, foliage and/or bark gleaning insectivores, the major prey groups of the babblers comprises of relatively more terrestrial (i.e., Coleoptera, Hymenopter,a and Araneae of understory level, similar to Mansor et al (2018), except Blattodea) rather than aerial arthropods (but see Mansor et al 2021). The abundance of Hymenoptera such as ants and Araneae (spiders) on the forest floor (Griffiths et al 2018;Hartshorn et al 2021) as well as those in the aerial leaf litter (Mansor et al 2019) might be a reason that they formed a major portion of the babblers' diet.…”
Section: Diet Compositionmentioning
confidence: 99%
“…Taking a high‐resolution approach, and in agreement with previous studies, we found high dietary overlap between predator species; however, M. sodalis generally preyed upon a greater richness of prey taxa, while M. septentrionalis preyed upon a greater range of sizes. In Malaysian babblers, dietary flexibility facilitates niche segregation and coexistence with low dietary overlap (Mansor et al, 2021). In this study, high dietary overlap was apparent at the OTU level and even moreso at the prey‐size type level (Table 2), suggesting little niche segregation.…”
Section: Discussionmentioning
confidence: 99%
“…As complete competitors cannot coexist [ 1 , 2 ], the niche theory predicts that animals will segregate in the n-dimensional niche hyper-volume to avoid both inter- and intra-specific competition (e.g., [ 3 , 4 , 5 , 6 ]). Segregation can be achieved through differences in foraging behavior [ 7 ], habitat use, morphological adaptation or dietary specialization [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%